Persepsi Perawat dalam Perawatan Holistik Islami pada Bayi Resiko Tinggi di Rumah Sakit Sari Asih Sangiang - Farida Hanum Siregar; Indra Tri Astuti; Nopi Nur Khasanah (PT Pustaka Cendekia Publisher, 2026)
This study was driven by the need to implement Islamic holistic nursing in caring for high-risk infants requiring spiritual support in Muslim families. The purpose of this research was to describe nurses’ perceptions of Islamic holistic nursing practice at Sari Asih Sangiang Hospital. A descriptive quantitative design with a survey approach was employed. The population included 33 nurses from NICU, PICU, and pediatric wards using total sampling. Data were collected using a 10-item Likert questionnaire validated (r count > 0.333) and reliable (Cronbach’s α = 0.978). Univariate analysis used frequency and percentage distribution. The results showed that 93.9% of nurses had high perceptions of Islamic holistic nursing, 3.0% moderate, and 3.0% low. The conclusion highlights that nurses demonstrate strong readiness to integrate Islamic values such as prayer, remembrance, and proper conduct in critical infant care, supporting the development of standardized Sharia-based nursing practices.